HUBUNGAN ANGKA KECUKUPAN ZAT BESI DAN VITAMIN C DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Andi Hikma Padaunga; Sitti Mukarramah (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Anemia in pregnancy is one of the conditions where the hemoglobin level is lower than the normal level, which is <11 g /dl. The nutritional adequacy rate of pregnant women have a role in the process of anemia. Diversity in food consumption have an important role in helping to increase iron substance absorption in the body. Objective: To determine the relationship of iron substance and vitamin C adequacy rates with the incidence of anemia in third trimester pregnant women. Methods: This study is observational research with a cross sectional study approach. Sampling by using simple random sampling method for 47 subjects pregnant women of third trimester was determined by using the Lemeshow formula. Data analysis using Chi-Square test.